A review of the management of HIV positive pregnant patients in a District General Hospital setting. (16th November 2010) - Usman, S; Farthing, S; Dixit, A
Abstract : Background: Diagnosis of HIV infection in pregnancy and treatment with antiretrovirals is key to preventing vertical transmission. However, treatment has been shown to be associated with increased incidence of pregnancy complications such as pre-eclampsia, gestational diabetes and preterm labour Objective: To review the pregnancy outcome of HIV positive (+ve) pregnant patients in a district general hospital setting. Method: A 5-year (2005–2009) prospective population study of all HIV+ve pregnant women delivering at West Middlesex University Hospital. Results: 62 cases analysed – 41 diagnosed prepregnancy; 21 during pregnancy. Mean age – 30yrs (16–44) and most (89%) of Black African origin. 61 received HAART with 1 woman receiving zidovudine monotherapy. 74% commenced HAART before 24 weeks – 26 prepregnancy, 20 at <24 weeks. Viral load (VL) was undetectable at start of treatment in 26(42%). Of the 36(58%) with detectable VL, 20(56%) achieved undetectable VL by 36 weeks. 11(18%) delivered preterm (<37weeks) – abruption in 3(5%) with no identifiable cause in 8(13%). 3(5%) women developed preeclampsia and 2(3%) gestational diabetes. There were no side effects from treatment other than asymptomatic transaminitis in 5 women. Vaginal delivery was planned for 20(32%) women – 3(15%) of these needed Emergency Caesarean Sections (1 for abruption; 2 for failure to progress). No vertical transmission occurred. Conclusion: With multidisciplinary input to care of HIV+ve pregnant women, most achieve good pregnancy outcomes with a fair proportion achieving vaginal delivery. There is an increased incidence of idiopathic preterm delivery possibly related to HAART; this needs further exploration in larger studies.